Designing a Promotional Video as a Tool to Promote Swiss-Belinn Airport Hotel Surabaya to its Target Market - Nathalia Cindy Cindy (Institute of Research and Community Outreach - Petra Christian University, 2020)
This is a Creative Thesis Final Project Report on a problem at Swiss-Belinn Airport Hotel Surabaya (SAHS). SAHS is a hotel that is located strategically in close proximity to Juanda Airport. The hotel has three types of rooms and provide various facilities, such as restaurant, pool etc. The target markets for these products are people who need meeting rooms, and are away on business trips, vacations, and transit. However, the hotel is struggling to reach out to individual guests. Thus, in order to effectively introduce and inform the hotel to a wider population, a tool is needed. A Promotional Video (PV) is a short video or movie to promote a product or service to potential customers. PV can highlight the USP of the hotel. However, due to the current pandemic, creating the promotional video is unattainable. Thus, this thesis would cover interviews for the data and/until the act of creating the plotline for the promotional video.Keywords: Promotional tool, promotional video, USP, target market